HUBUNGAN PENGETAHUAN BANTUAN HIDUP DASAR TERHADAP TINGKAT MOTIVASI MAHASISWA DALAM MENOLONG PASIEN HENTI JANTUNG PADA MAHASISWA PRODI NERS TINGKAT III STIKES SANTA ELISABETH MEDAN - Mardiati Barus (STIKes Santa Elisabeth Medan, 2017)
The knowledge of basic life assistance becomes a fundamental matter of handling victims suffering from cardiac arrest. With the knowledge of basic life assistance and supported by the motivation of rescuer in handling victims suffering from cardiac arrest, it is expected that the mortality rate of cardiac arrest incident frequently occurring particularly outside the hospital may be reduced significantly. Goals : The research aimed to know the connection between the knowledge of basic life assistance and the motivation level of students in helping patients suffering from cardiac arrest in prodi ners level III students of STIKes Santa Elisabeth Medan. Methods : The research design used the corelational descriptive method, with the number of samples being 75 respondents. Result : The results of research showed that the knowledge of students on basic life assistance was good (100%) and the level of motivation in helping patients suffering from cardiac arrest was high (100%). From the results of Spearmen rank, the value of p=0.000 (p<0.05) and the correlation coefficient of 0.997 were obtained, meaning that there was a strong connection between the knowledge of basic life assistance and the motivation level of students in helping patients suffering from cardiac arrest in prodi ners level III students of STIKes Santa Elisabeth Medan. Conclution : It is expected that students would maintain good knowledge of basic life assistance and their motivation would be increasingly higher to perform basic life assistance in patients suffering from cardiac arrest.